Somatic status of adolescent girls with gynecological disorders born with low and excessive weight - I. Tuchkina; N. Pylypenko; M. Tuchkina; O. Piontkovska; N. Romanova; I. Kachaylo (Kazimierz Wielki University, 2022)
In modern conditions, health problems (somatic, reproductive, mental) of adolescent girls occupy a special place in the health care system, as a reserve in reducing maternal and infant mortality, maintaining the fertility of the expectant mother. The aim. To study the frequency and character of extragenital diseases of adolescent girls with gynecological pathology, born with low and excessive body weight. Materials and methods. The project design is a population-based prospective cohort study. To achieve the goal and the implementation of the tasks, a prospective examination of girls and adolescent girls born with deficiency or excess body weight was carried out. The sample size was 77 people. Additionally, statistical processing was carried out using the Excell software. Results. Thus, the study of somatic health indicates its deterioration in the groups of girls born with polar values ​​of body weight. In groups 1 and 3, infectious diseases were identified, which can serve as a starting point in the development of reproductive system disorders. In girls of group 1, mumps prevailed (20.0%), which could cause damage to the follicular apparatus, while in group 3, girls were more likely to have influenza (25.8%), the virus of which has a damaging effect not only on the structure of the ovaries, but also on endometrium. Conclusions. Comparative analysis of the structure of somatic morbidity made it possible to identify the most significant pathology characteristic of each of the groups. Girls born with a large body weight have an increased risk of endocrine pathology. In girls born with low body weight, somatic diseases associated with manifestations of diseases of the musculoskeletal system prevail. This dictates the need to single out girls born with polar values ​​of body weight in the risk group for the development of somatic pathology and requires complex therapeutic and prophylactic measures.